Students’ and Teachers’ Beliefs on English Language Teaching: A Study in One Islamic Boarding School - Mustika Rini (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
This study was done to find out (1) whether there was a significant difference between students and teachers belief in one Islamic boarding school in Palembang, (2) the teacher beliefs on English language teaching in Islamic boarding school in Palembang, and (3) students’ beliefs on English language teaching in one Islamic boarding school Palembang. This study employed a mixed method research design. Participants for collecting quantitative data were 55 students and 1 teacher, meanwhile the participants for qualitative data were 6 students and 1 teacher. In order to collect the quantitative data, questionnaire was used, and for qualitative data, interview was used. These instruments were used to find the difference of beliefs between students and teacher on English language teaching. From this study, it was found out the difference beliefs between students and teacher on English language teaching toward communicative language strategy and target language use. Moreover, from the interview results, the differences between students and teachers’ beliefs in communicative language strategies and target language use were also found.